2018
DOI: 10.1111/srt.12454
|View full text |Cite
|
Sign up to set email alerts
|

Does dietary fluid intake affect skin hydration in healthy humans? A systematic literature review

Abstract: Additional dietary water intake may increase stratum corneum hydration. The underlying biological mechanism for this possible relationship is unknown. Whether this association also exists in aged subjects is unclear. Research is needed to answer the question whether increased fluid intake decreases signs of dry skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…The stratum corneum (SC) layer of the epidermis is the primary location of the barrier function; however, both the dermis and the multilayered epidermis are important for maintenance of barrier integrity [32]. Measurements for skin barrier function and hydration include transepidermal water loss (TEWL), SC hydration, “deep” skin hydration, clinical evaluation of dryness, roughness and elasticity, skin relief parameter, the average roughness, evaluation of skin surface morphology, skin smoothness and roughness, extensibility, sebum content, and skin surface pH [24].…”
Section: Hydration and Health Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…The stratum corneum (SC) layer of the epidermis is the primary location of the barrier function; however, both the dermis and the multilayered epidermis are important for maintenance of barrier integrity [32]. Measurements for skin barrier function and hydration include transepidermal water loss (TEWL), SC hydration, “deep” skin hydration, clinical evaluation of dryness, roughness and elasticity, skin relief parameter, the average roughness, evaluation of skin surface morphology, skin smoothness and roughness, extensibility, sebum content, and skin surface pH [24].…”
Section: Hydration and Health Outcomesmentioning
confidence: 99%
“…For hydration and skin health, a 2018 systematic review was identified [24], which included five intervention studies. Of these studies, four measured surface hydration and reported increased SC hydration following additional intake of 2 L daily of water over a period of 30 days [33,34,35] or additional intake of 1 L per day for a period of 42 days [36].…”
Section: Hydration and Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous factors which may cause skin dryness like endocrine disorders, genetic predisposition, climate or medication (Paul et al, ; White‐Chu & Reddy, ). Fluid intake is believed to affect the skin hydration as well, but the empirical evidence supporting this association is week (Akdeniz, Tomova‐Simitchieva, Dobos, Blume‐Peytavi, & Kottner, ), especially in care‐dependent aged adults (Akdeniz, Boeing, et al, ).…”
Section: Introductionmentioning
confidence: 99%